2017
DOI: 10.1177/1087054717733043
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Change in a Parent Training Program for Early ADHD Difficulties: The Role of Parental Strategies, Parental Self-Efficacy, and Therapeutic Alliance

Abstract: Parental self-efficacy and reductions in negative parenting may mediate change in PT, but more fine-grained time-lagged analyses are needed to establish causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
3
13
1
Order By: Relevance
“…Finally, do we expect change to occur in full already during the intervention, or do parents perhaps need more time to practice and implement the strategies and tips they learn and receive during the sessions? Our findings and those of others might suggest most change occurs already during the intervention and then sustains over time (Rimestad et al, 2017;Weeland et al, 2018).…”
Section: How It Work: Mediation By Parental Behavior and Parental Afsupporting
confidence: 79%
See 3 more Smart Citations
“…Finally, do we expect change to occur in full already during the intervention, or do parents perhaps need more time to practice and implement the strategies and tips they learn and receive during the sessions? Our findings and those of others might suggest most change occurs already during the intervention and then sustains over time (Rimestad et al, 2017;Weeland et al, 2018).…”
Section: How It Work: Mediation By Parental Behavior and Parental Afsupporting
confidence: 79%
“…From a theoretical point of view, we do not expect single-unidirectional causal relations between parenting practices and child behavior; likewise, the putative mechanisms of change underlying parenting intervention might also be more complex (Burke & Loeber, 2016; Kazdin, 2007; Rimestad, O'Toole, & Hougaard, 2017; Settipani, O'Neil, Podell, Beidas, & Kendall, 2013). Although BPT interventions such as IY directly target parenting behavior (and do not directly target child behavior), it is still possible that changes in child behavior during the intervention precede (further) changes in parenting behavior or that both changes in parenting and child behavior are explained by another (unmeasured) variable.…”
Section: How It Work: Mediation By Parental Behavior and Parental Afmentioning
confidence: 92%
See 2 more Smart Citations
“…Conversely, harsh or inconsistent parenting has been posited to fuel oppositionality and other disruptive behaviors. Accordingly, a recent study (Rimestad, O'Toole, & Hougaard, 2017) found that heightened parental self-efficacy and diminished negative parenting mediated reductions in ADHD symptoms. Forehand et al (2017) failed to find evidence implicating parent ADHD symptoms as a treatment moderator; otherwise few moderator variables have been identified in research involving BPT in preschool children with ADHD (Daley, Jones, Hutchings, & Thompson, 2009).…”
Section: Treatment Moderators and Mediatorsmentioning
confidence: 99%